A Note on The Genus Evolvulus (Convolvulaceae) In Java, Indonesia - Arifin Surya Dwipa Irsyam; Muhammad Rifqi Hariri; Rina Ratnasih Irwanto; Wendy Achmad Mustaqim (Jurnal Biodjati, 2020)
According to the Flora of Java, there is only one species of Evolvulus in Java, namely Evolvulus alsinoides. Since then, a second species was reported in 2017 from Universitas Indonesia, Depok, West Java, as an alien naturalized species. Some recent field studies have been conducted to provide updated taxonomic information of the genus on this island. The field observations were carried out in Banten, Jakarta, West Java, Jogjakarta, and East Java from March to December 2019. The herbarium studies were also conducted in Herbarium Bogoriense, Herbarium of Bogor Botanic Gardens, Herbarium Bandungense, and Herbarium of the Department of Biology, Universitas Indonesia. Our study reveals one newly recorded species of Evolvulus in Java already grown in cultivation, namely E. glomeratus Nees & Mart. subsp. grandiflorus (Parodi) Ooststr. Besides that, Evolvulus nummularius is now also reported to occur in other sites of West Java and extended to Central Java. An updated key to Evolvulus in Java, descriptions to both species, photographs, and brief discussions are provided.